Intermittent adult ileocecal intussusception: a case report and review of literature. Issue 1 (February 2014) - de Clerck, F.; Pletinckx, P.; Claeys, D.; Muysoms, F.; Vergucht, V.; Burvenich, P.; Vanderstraeten, E.; Baert, D.; Monsaert, E.; Rasquin, K.; De Cock, G.; Van Steenkiste, C.
Abstract : We report the case of a 56-year-old male patient who was admitted to the emergency department with crescendo abdominal pain since 2 weeks. In the past 2 years, similar but less pronounced episodes were present, each time resolving spontaneously after spasmolytic drugs. Abdominal ultrasound revealed an ileocecal intussusception. An attempt for preoperative reduction was partially successful. A colonoscopy was performed and showed a tubulovillous adenomatous polyp with high-grade dysplasia, but subsequent right hemicolectomy revealed an underlying cecal adenocarcinoma. The combination of the low incidence and the non-specific symptoms of ileocecal intussusception in the adult makes this entity difficult to diagnose. In most cases, modern imaging techniques such as CT scan, ultrasound, or MRI make the correct preoperative diagnosis. Especially when colonic involvement is present, suspicion of a malignant lead point (i.e. culprit lesion) is primordial. The therapeutic strategy depends on several variables and asks for a patient-tailored, selective approach mostly involving surgery. Based on this case and a short review of literature, we discuss the clinical presentation, diagnostic tools, treatment, and challenges of adult ileocecal intussusception.